PENERAPAN HUKUM SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2015 TERHADAP PENGGUNAAN NARKOBA UNTUK DIRI SENDIRI - Siagian, Ahmad Rifa’i (UM.Tapanuli Selatan, 2026)
Drug abusers who are dependent will certainly continue to seek narcotics to meet their narcotic needs, even though they are expensive and prohibited by law. Supreme Court Circular Letter Number 3 of 2015 indicates that judges who wish to use the Circular Letter must be able to